On Markov property of stochastic processes - Grigelionis, B. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Григелионис. О марковском свойстве случайных процессов B. Grigelionis. Apie atsitiktinių procesų Markovo savybę